Impact of Climate Change and Human Activities on Runoff and Drought in Manas River Basin - XIAO Senyuan; SU Jun; YANG Guang; LIU Bing; ZHANG Di; QIU Zehao; LUO Yajie; HUANG Jingjing (Renmin Zhujiang)
On the basis of the monthly precipitation and runoff data of Manas River Basin from 1956 to 2020,the Mann-Kendall nonparametric test method,double cumulative curve method,and standardized runoff index (SRI) are adopted to reveal the interannual variation trend of watershed runoff and quantitatively describe the contribution proportion of climate change and human activities to watershed runoff change.In addition,the characteristics of seasonal drought change are explored under the influence of climate change and human activities.The results indicate that:① the annual runoff of Manas River Basin shows an upward trend,and a significant mutation occurred in 1995;② Climate change is the main factor leading to the increase in runoff in Manas River Basin,and the contribution rates of climate change and human activities to the increase in runoff are 56.73% and 43.37%,respectively;③ On a seasonal scale,in contrast with the impact of climate change,human activities reduce the frequency of drought events in the basin and improve the drought situation in winter.In the meanwhile,however,farmland irrigation in spring consumes enormous water resources,which results in the trend of drought in the basin in spring.